2020
DOI: 10.1101/2020.12.22.20248259
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Understanding Covid-19 misinformation and vaccine hesitancy in context: Findings from a qualitative study involving citizens in Bradford, UK

Abstract: BackgroundCovid-19 vaccines can offer a route out of the pandemic, yet initial research suggests that many are unwilling to be vaccinated. A rise in the spread of misinformation is thought to have played a significant role in this vaccine hesitancy. In order to maximise vaccine uptake it is important to understand why misinformation has been able to take hold at this time and why it may pose a more significant problem within certain populations and places.ObjectiveTo understand people’s Covid-19 beliefs, their… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(91 citation statements)
references
References 33 publications
3
86
1
1
Order By: Relevance
“…These results highlight a much higher level of vaccine hesitancy in ethnic minorities, those living in deprived areas and those that distrust the NHS. These findings strengthen the key messages from recent qualitative work -that there is an urgent need to tackle the overwhelming misinformation about COVID-19 that is leading to uncertainty and confusion about the need for the vaccine, and in the worst cases, a belief that the vaccine should not be accepted 2 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results highlight a much higher level of vaccine hesitancy in ethnic minorities, those living in deprived areas and those that distrust the NHS. These findings strengthen the key messages from recent qualitative work -that there is an urgent need to tackle the overwhelming misinformation about COVID-19 that is leading to uncertainty and confusion about the need for the vaccine, and in the worst cases, a belief that the vaccine should not be accepted 2 .…”
Section: Discussionsupporting
confidence: 78%
“…However, since the beginning of the COVID-19 pandemic there has been what the World Health Organisation has called an 'infodemic': an overwhelming amount of information about COVID-19, much of it unchecked and uncontrolled and spread through social media channels 1 . Recent qualitative research has demonstrated that this overwhelming and contradictory information about COVID-19 has caused confusion, distrust and distress 2 . Significantly, this study found that the greater these feelings of confusion and distress, the less positive people were about COVID-19 vaccination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, surveys which specifically asked COVID-19 vaccine hesitant participants their reason for vaccine refusal or delay consistently report that concerns over safety and efficacy are among the most common reasons given (Callaghan et al, 2021;Fisher et al, 2020;Frank & Arim, 2020;Ruiz & Bell, 2021;Yigit et al, 2021;Yoda & Katsuyama, 2021). Similarly, qualitative research has also highlighted these concerns as reported drivers of COVID-19 vaccine hesitancy among minority and at-risk groups (Lockyer et al, 2020;Momplaisir et al, 2021;Williams et al, 2020). Such concerns may be fuelled by COVID-19 vaccine misinformation (Hotez, 2020) and recent research has identified susceptibility to misinformation as a correlate of COVID-19 vaccine hesitancy (Roozenbeek et al, 2020).…”
Section: Beliefs About Covid Vaccines and Vaccine Hesitancymentioning
confidence: 99%
“…Since the beginning of the COVID-19 pandemic, there has been over-billing unchecked information especially through social media channels termed "infodemic" by the WHO [15]. The recent quality research has shown that unchecked infodemic about COVID-19 has created confusion, distrust and stress among the general public [16]. The most important myth rife on social media regarding COVID-19 vaccination is making people impotent sexually.…”
Section: The Covid-19 Vaccination Determinantsmentioning
confidence: 99%